2010
DOI: 10.1111/j.1751-0813.2010.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cysticercus bovis in Australian cattle

Abstract: Occasional, isolated diagnoses of beef measles are still made in most states of Australia, but since the last regional surveys were conducted 30 years ago, when the estimated prevalence was 50 to 200 per 100,000 cattle slaughtered, the parasite has become extremely rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
2
4
0
1
Order By: Relevance
“…This suggests lack of uniformity in meat inspection and documentation even among abattoirs in Israel. This finding is in line with other results shown in reports conducted around the world including Europe, Africa, Australia and America where the prevalence ranged greatly even in the same country (Pawlowski and Schultz, 1972; Cabaret et al., 2002; Opara et al., 2006; Kebede, 2008; Pearse et al., 2010). As mentioned before, all of these data are based on meat inspection, which has a low sensitivity for the detection of C. bovis (McCool, 1979; Kyvsgaard et al., 1990).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests lack of uniformity in meat inspection and documentation even among abattoirs in Israel. This finding is in line with other results shown in reports conducted around the world including Europe, Africa, Australia and America where the prevalence ranged greatly even in the same country (Pawlowski and Schultz, 1972; Cabaret et al., 2002; Opara et al., 2006; Kebede, 2008; Pearse et al., 2010). As mentioned before, all of these data are based on meat inspection, which has a low sensitivity for the detection of C. bovis (McCool, 1979; Kyvsgaard et al., 1990).…”
Section: Discussionsupporting
confidence: 93%
“…As the time required for Cysticercus development is at least 6 weeks, it is impossible that the calves were infected during their quarantine. Australian data from the 1960s points on a prevalence of 0.21% of BC (Fewster, 1967) and a recent study from 2008 found a dramatically lower prevalence of only 0.0002% in exporting abattoirs (Pearse et al., 2010). This may imply that these calves were infected in the ship during transport to Israel or in the pre‐shipping quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to comment on the first national abattoir survey of metacestodes of Taenia saginata (aka Cysticercus bovis (beef measles)) in cattle in Australia 1 . We agree with the conclusions of this study, which found no evidence of T. saginata in ∼500,000 slaughtered cattle from across Australia during a single month.…”
supporting
confidence: 71%
“…Pearce et al. recently concluded that bovine cysticercosis in Australian cattle was ‘extremely rare’ . However, a characteristic feature of bovine cysticercosis in countries where the parasite occurs uncommonly in cattle, such as Australia, is ‘cysticercosis storms’, which occur as a result of sudden exposure of immunologically naïve cattle to the eggs of T. saginata .…”
mentioning
confidence: 99%